SCL/TAL1 cooperates with Polycomb RYBP-PRC1 to suppress alternative lineages in blood-fated cells - Chagraoui, Hedia; Kristiansen, Maiken S.; Ruiz, Juan Pablo; Serra-Barros, Ana; Richter, Johanna; Hall-Ponselé, Elisa; Gray, Nicki; Waithe, Dominic; Clark, Kevin; Hublitz, Philip; Repapi, Emmanouela; Otto, Georg; et al. (Nature communications, 2018)
During development, it is unclear if lineage-fated cells derive from multilineage-primed progenitors and whether active mechanisms operate to restrict cell fate. Here we investigate how mesoderm specifies into blood-fated cells. We document temporally restricted co-expression of blood ( Scl/Tal1 ), cardiac ( Mesp1 ) and paraxial ( Tbx6 ) lineage-affiliated transcription factors in single cells, at the onset of blood specification, supporting the existence of common progenitors. At the same time-restricted stage, absence of SCL results in expansion of cardiac/paraxial cell populations and increased cardiac/paraxial gene expression, suggesting active suppression of alternative fates. Indeed, SCL normally activates expression of co-repressor ETO2 and Polycomb-PRC1 subunits (RYBP, PCGF5) and maintains levels of Polycomb-associated histone marks (H2AK119ub/H3K27me3). Genome-wide analyses reveal ETO2 and RYBP co-occupy most SCL target genes, including cardiac/paraxial loci. Reduction of Eto2 or Rybp expression mimics Scl -null cardiac phenotype. Therefore, SCL-mediated transcriptional repression prevents mis-specification of blood-fated cells, establishing active repression as central to fate determination processes. Mechanisms that operate during embryonic development to restrict cell fate are currently under investigation. Here the authors characterise the role of SCL/TAL1 at the onset of blood specification in embryonic development using mouse EB differentiation culture as a model system.